Combination of Sorafenib, Camrelizumab, Transcatheter Arterial Chemoembolization, and Stereotactic Body Radiation Therapy as a Novel Downstaging Strategy in Advanced Hepatocellular Carcinoma With Portal Vein Tumor Thrombus: A Case Series Study - Huang, Yun; Zhang, Zeyu; Liao, Weijun; Hu, Kuan; Wang, Zhiming (Frontiers in Oncology, 2021)
Background and aim: Although the treatment effect and availability of therapeutic options for advanced hepatocellular carcinoma (HCC) are limited, the downstaging strategy may improve patient prognosis. This study aimed to investigate the potential of combination therapy as a downstaging strategy for treating advanced HCC with portal vein tumor thrombus (PVTT). Methods: This retrospective case series included patients having advanced HCC with PVTT, who received the combination therapy of sorafenib, camrelizumab, transcatheter arterial chemoembolization (TACE), and stereotactic body radiation therapy (SBRT) from January 2019 to December 2019 in Xiangya Hospital, Central South University. The downstaging rate, treatment responses, progression-free survival (PFS), overall survival (OS), disease control rate, and toxicities were evaluated. Results: Of the 13 patients, HCC downstaging was achieved in 4 (33.3%) patients who later received hepatectomy. The overall response rate was 41.7%, and the disease control rate was 50.0%. The median PFS time was 15.7 months, with a 1-year PFS rate of 58.3%, whereas the median OS was not reached after 1 year (1-year OS, 83.3%). No severe adverse events or grade 3–4 adverse effect was observed in 12 of the 13 enrolled patients; therapy had to be discontinued in only one patient due to adverse events, who was excluded from the study. The most common adverse effect was fever (n = 4, 33.3%), followed by skin reaction (n = 3, 25%). Conclusion A combination therapy comprising sorafenib, camrelizumab, TACE, and SBRT is an effective downstaging strategy for advanced HCC with PVTT and is associated with few adverse events.